Фома Аквинский: [пер. с пол.] / Юзеф Боргош - Боргош Юзеф (Мыслители прошлого, 1975)
Экземпляры: КХ (20121022) / Инвентарный номер: 602541 / Цена: 0.23 / Сис.шифр: 1Ф / Авт.знак: Б 82 / ГРНТИ: 02 / ББК: 87